Controllable synthesis of nickel nanowires and its application in high sensitivity, stretchable strain sensor for body motion sensing. Issue 17 (19th April 2018) - Wang, Shan; Chen, Kaifeng; Wang, Min; Li, Haosheng; Chen, Guorui; Liu, Jian; Xu, Luhang; Jian, Yue; Meng, Chengda; Zheng, Xiaoyi; Liu, Suyu; Yin, Chong; et al.
Abstract : Sandwich-structured strain sensor based on high L / D ratio NiNWs and Ecoflex with high sensitivity and stretchability. Abstract : A facile, low-cost magnetic field-assisted chemical reduction method was proposed for synthesizing nickel nanowires (NiNWs) with both controllable diameter and high length to diameter ( L / D ) ratio at temperature as low as 60 °C. NiNWs with diameter as low as 180 ± 21 nm and L / D ratio as high as 300 were achieved by controlling the reaction temperature, NiCl2 concentration and the quantity of reductant in a magnetic field of 170 mT. Based on the NiNWs, a high-sensitivity and stretchable strain sensor with sandwich structure consisting of NiNWs and Ecoflex elastomer was proposed. Gauge factor as high as 200 was demonstrated up to a strain of 100%. Applications of the sensor in detecting body motion including finger gestures, facial expressions and different phonations are presented. This study provides a promising solution for smart sensors for next generation robotics as well as for human–machine interfacing applications.